Benchmarks of Duration and Magnitude of Opioid Consumption After Common Spinal Procedures: A Database Analysis of 47, 823 Patients. Issue 23 (1st December 2019) - Cook, David J.; Kaskovich, Samuel; Pirkle, Sean; Ho, Alisha; Conti Mica, Megan; Shi, Lewis; Lee, Michael
Abstract : Study Design: A retrospective cohort study performed in a nationwide insurance claims database. Objective: This study aimed to examine duration and magnitude of postoperative opioid prescriptions following common spinal procedures. Summary of Background Data: Postoperative opioid prescription practices vary widely among providers and procedures and standards of care are not well-established. Previous work does not adequately quantify both duration and magnitude of opioid prescription. Methods: Forty seven thousand eight hundred twenty three patients with record of any of four common spinal procedures in a nationwide insurance claims database were stratified by preoperative opioid use into three categories: "opioid naive, " "sporadic user, " or "chronic user, " defined as 0, 1, or 2+ prescriptions filled in the 6 months preceding surgery. Those with record of subsequent surgery or readmission were excluded. Duration of opioid use was defined as the time between the index surgery and the last record of filling an opioid prescription. Magnitude of opioid use was defined as milligram morphine equivalents (MME) filled by 30 days post-op, converted to 5 mg oxycodone pills for interpretation. Results: Opioid naive patients were less likely than chronic opioid users to fill any opioid prescription after surgery (63–68% naive vs. 91–95% chronic, P  < 0.001), and when they did, their prescriptions were smaller in magnitude (76–91 pills naive vs. 127–152 pills chronic). One year after surgery, 15% to 18% of opioid naive and 50% to 64% of chronic opioid users continued filling prescriptions. Conclusion: Opioid naive patients use less postoperative opioids, and for a shorter period of time, than chronic users. This study serves as a normative benchmark for examining postoperative opioid use, which can assist providers in identifying patients with opioid dependence. Importantly, this work calls out the high risk of opioid exposure, as 15% to 18% of opioid naive patients continued filling opioid prescriptions 1 year after surgery. Level of Evidence: 3 Abstract : This study uses a nationwide database to examine patients' postoperative opioid use after four common spine procedures. Patients with preoperative opioid use maintain higher durations and magnitudes of opioid prescription filling after surgery. Results suggest that 15% to 18% of patients without history of opioid use develop opioid use disorder after surgery.